Content analysis of TEOG mathematics items based on MONE attainments, TIMSS levels, and reformed Bloom Taxonomy TEOG sınavı matematik sorularının MEB kazanımlarına, TIMSS seviyelerine ve yenilenen Bloom Taksonomisine göre incelenmesi - Başol, Gülşah; Balgalmış, Esra; Karlı, Meltem Gülsüm; Öz, Fatma Betül (Journal of Human Sciences, 2016)
The aim of the study is to classify and evaluate the mathematics test items in the Transition System of Secondary Education (TEOG) exam according to the attainment levels of the Secondary School National Mathematics Curriculum, TIMSS levels and Bloom’s renewed taxonomy. The study covers the TEOG math items between the years 2013 and 2016. In data analysis, content analysis, a qualitative research technique, was applied. For the classification of the materials, the acquisition list of the eighth grade mathematics course prepared by MONE, the scheme of TIMSS levels, and Bloom’s Renewed Taxonomy were used. Booklet A was taken as a base for the classification for each exam. According to findings, in the TEOG exams applied between 2013-2016, while the TEOG exam was consistently asking questions in certain examinations from certain acquisitions, it was seen that no questions were asked from some of the acquisitions. When the 260 mathematical items in the TEOG exams classified according to TIMSS levels, of the items 33.8% were at "Level 1", 45% were at "Level 2", 19.6% were at "Level 3" and 1.5% were at "Level 4 ". Parallel with these findings, when TEOG mathematics items classified according to Restructured Bloom Cognitive Domain Taxonomy, of the items17,69% were at "Remembering", 18,46% were at "Understanding", 54,23% were at "Implementation", 5,76% were at "Analysis" and 3.6% were at "Evaluation" levels. The results indicated that the majority of the math items in the TEOG exams were at the “Application level” and the number of items in the "Reasoning level" was limited. Such exams, as TEOG, directing students high school in consistent with their cognitive level, should measure higher order skills, as well. Özet Çalışmanın amacı, Temel Eğitimden Ortaöğretime Geçiş Sistemi (TEOG) sınavı matematik test maddelerinin, Milli Eğitim Bakanlığı Ortaokul Matematik Programı kazanımlarına, TIMSS düzeylerine ve Bloom’un Yenilenmiş Bilişsel Alan Taksonomisine göre sınıflandırılıp değerlendirilmesidir. 2013-2016 yılları arasında TEOG sınavı matematik soruları araştırma kapsamında incelenmiştir. Verilerin analizinde nitel araştırma tekniklerinden içerik analizi kullanılmıştır. Maddelerin sınıflandırılması için MEB tarafından hazırlanan sekizinci sınıf matematik dersine ait kazanım listesi, TIMSS sorularının düzeylerini gösteren TIMSS düzeyleri şeması ve Bloom’un Yenilenmiş Bilişsel Alan Taksonomisi kullanılmıştır. Sınıflamada her bir TEOG sınavının matematik temel alanına ait A kitapçıkları temel alınmıştır. Bulgulara göre 2013-2016 yılları arasında uygulanan TEOG sınavlarında belli kazanımlardan her sınavda soru sorulurken, bazı kazanımlardan hiç soru sorulmadığı görülmüştür. TEOG sınavlarında sorulan 260 matematik sorusu TIMSS düzeylerine göre sınıflandırıldığında %33,8’i “Düzey 1”, %45’i “Düzey 2”, %19,6’sı “Düzey 3” ve %1,5 ’i “Düzey 4”de yer aldığı görülmüştür. TEOG matematik test maddelerinin; Yeniden Yapılandırılan Bloom Bilişsel Alan Taksonomisine göre dağılımına bakıldığında soruların %17,69’u “Hatırlama”, %18,46’sı “Anlama”, % 54,23’ü “Uygulama”, %5,76’sı “Analiz” ve %3,46’sı “Değerlendirme” bilişsel alan basamaklarında olduğu görülmüştür. Sonuçlara göre TEOG matematik test maddelerinin çoğunluğunun “Uygulama” basamağında olduğu, “Analiz” ve “Değerlendirme” basamaklarındaki madde sayısının sınırlı olduğu görülmüştür. TEOG gibi öğrencilerin bilişsel düzeylerine göre liselere yönlendirilmesinin hedeflendiği bir sınavdaki sorular bu amaca uygun olarak üst düzey bilişsel becerileri de ölçecek şekilde hazırlanmalıdır.